Mosquito-borne diseases in urban East African Community region: a scoping review of urban typology research and mosquito genera overlap, 2000-2024 - Joseph, Noel K.; Mumo, Eda; Morlighem, Camille; Macharia, Peter M.; Snow, Robert W.; Linard, Catherine (Frontiers in Tropical Diseases, 2024)
BackgroundGrowing concerns about mosquito-borne diseases (MBDs) in urban settings have prompted renewed urgency for collaborative and active mosquito surveillance programs. This literature review collates entomological data from five East African Community (EAC) countries, studying the definitions of urban settings, co-occurrence of Anopheles, Aedes and Culex mosquito genera and their infection rates to provide a wholistic understanding of MBDs in urban EAC.MethodsA literature search following the PRISMA-ScR guidelines was conducted in EMBASE, MEDLINE, PubMed, Web of Science and Scopus databases to identify entomological studies conducted in urban and peri-urban settings since 2000. Data on urban and peri-urban settings definitions, presence records and infection rates of Aedes, Culex and Anopheles mosquitoes were compiled and presented.ResultsA hundred and five articles were included in the review. Diverse definitions of urban landscapes emerged, emphasizing (i) distinct characteristics for dichotomous delineation from rural settings (e.g., population density) and (ii) urban-peri-urban continuum integrating spatial variations in urban features associated with MBDs (e.g., planned/unplanned neighbourhoods). Mosquito ecology data derived from 88 sites, comprising 45 urban, 25 peri-urban, 14 mixed settings and four slums, reported 91 mosquito species, including 32% Culex, 31% Aedes, and 25% Anopheles genera. Other co-occurring genera, such as Coquillettidia and Mansonia, represented 12% between 2000 and 2024. Intricate co-occurrence patterns among Aedes, Culex and Anopheles genera linked to habitat preference and climatic conditions (temperature and precipitation) were observed. The average infection rates were estimated as 0.8% for yellow fever, 0.9% and 1.1% for urban and peri-urban P. falciparum sporozoites respectfully, 2.7% for Dengue, 5.3% for Chikungunya and 6.02% for flavivirus, indicating co-circulation of arboviruses among mosquito population.ConclusionOur synthesis presents an overview of the complexities of urban MBD research over the past two decades. Integrated assessment of MBDs dynamics in rapidly evolving urban environments is crucial to achieving healthier urban environments in East Africa.Systematic review registrationhttps://osf.io/a6s9j/.